Boablingin Sings of The Helong Soul : A Semiotic And Cultural Reading of A Traditional Song: English - Lasi, Apri Marleni; Isu, Rudolof Jibrael; Radja, Markus Dimu (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
This research explores the cultural, semiotic, and social meanings embedded in the traditional song "Boablingin", which originates from the Helong tribe of East Nusa Tenggara, Indonesia. As part of a rich oral tradition, the song plays a vital role not only in preserving musical heritage but also in transmitting values, beliefs, and the Helong people's worldview. Using a descriptive qualitative method, data were collected through documentation studies, in-depth interviews with local elders, and textual analysis of the lyrics. The findings reveal that Boablingin contains symbolic representations of nature, love, community solidarity, and ancestral reverence. These elements reflect the interconnectedness between humans and the environment, a fundamental aspect of Helong cosmology. Moreover, the song functions as a cultural text that reinforces ethnic identity, strengthens intergenerational transmission, and resists cultural erosion in the face of modernization. This study not only contributes to the preservation of intangible cultural heritage, but also offers a model for integrating semiotic analysis and ethnographic approaches in the study of indigenous music traditions.